Explaining Caregivers' Perceptions of Palliative Care Unmet Needs in Iranian Alzheimer's Patients: A Qualitative Study - Ashrafizadeh, Hadis; Gheibizadeh, Mahin; Rassouli, Maryam; Hajibabaee, Fatemeh; Rostami, Shahnaz (Frontiers in Psychology, 2021)
Introduction: The needs of Alzheimer's patients are very complex and diverse and many of them are considered unmet needs. Understanding and responding to the unmet and complex needs of Alzheimer's patients can affect the quality of care. Therefore, the present study aimed to explain the perception of formal and informal caregivers of the unmet needs of Iranian Alzheimer's patients. Methods: The present qualitative study employed a Directed Content Analysis approach and was conducted in Iran In 2020. This research was done through in-depth and semi-structured interviews with 19 qualified caregivers enrolled (11 informal caregivers and 8 formal caregivers) with the mean age of 46.05+10.98 years in a purposive sampling method. Interviews continued until data saturation. Data analysis was performed simultaneously with data collection. After recording and transcribing, the data were analyzed using the Elo & Kyngas method based on the National Consensus Project framework (NCP). Data management was done with MAXQDA software. In order to achieve the accuracy and validity of the study, the criteria presented by Lincoln & Guba Credibility, Dependability, Confirmability, and Transformability were considered and used. Results: The mean age of participants was 46.05±10.98. Participants in this study acknowledged that Alzheimer's patients need comprehensive needs management with a holistic approach to increase quality of life. This theme based on the National Consensus Project framework consists of 7 main categories including "Structure and processes of care", "Physical aspects of care", "Psychological and psychiatric aspects of care", " Social aspects of care", " Cultural aspects of care", "Care of the patient nearing the end of life" and "Ethical and legal aspects of care" with 16 subcategories. Conclusion: The findings of this study provide a deep understanding of the unmet needs of Alzheimer's patients in Iran. Identifying the unmet needs of patients can pave the way for the treatment team to provide effective solutions to meet the needs and empower caregivers to provide comprehensive care for patients.